2020
DOI: 10.18203/2320-1770.ijrcog20205216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anemia amongst HIV positive pregnant women in a tertiary Hospital in Nigeria

Abstract: Background: In pregnancy, anemia is associated with increased risk of both maternal and fetal morbidity and mortality especially in HIV situation. To determine the prevalence and determinants of anemia in HIV positive compared to HIV negative women.Methods: This was a cross sectional study carried out from June 2016 to December 2017 amongst pregnant women who presented to the antenatal clinic. Information on socio-demographic variables and laboratory test to determine the hemoglobin levels and CD4 count (for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Studies from different countries consider anemia a common problem for HIV/AIDS patients, making their life miserable: India (51.9%, 164/316) [23], China (55.15%, 255/462) [24], Indonesia with HAART-naïve and patients on HAART as 60.8% and 40.3%, respectively [25], Nepal (66.7%, 140/210) [26], and Uganda (67.38%, 95/141) [27]. In the above-mentioned studies, the rates of prevalence were much higher as compared with the finding of the present study, and other research showed relative lower findings, even though the number of patients included in the respective studies differed: Nigeria (36.6%, 128/350) [28], Northwest Ethiopia (16.2%, 43/265) [29], South Ethiopia (36.5%, 150/411) [30], United States (10.3%, 1,551/15,126) [31], and Ethiopia (31.0%, 2,504/8,079) [32]. The above differences in anemia prevalence might be due variations in nutritional status of patients, their family histories, diseases caused by a genetic disorder, the presence of current co-infections caused by either parasites or other diseases that can contribute to the occurrence of anemia.…”
Section: Discussioncontrasting
confidence: 73%
“…Studies from different countries consider anemia a common problem for HIV/AIDS patients, making their life miserable: India (51.9%, 164/316) [23], China (55.15%, 255/462) [24], Indonesia with HAART-naïve and patients on HAART as 60.8% and 40.3%, respectively [25], Nepal (66.7%, 140/210) [26], and Uganda (67.38%, 95/141) [27]. In the above-mentioned studies, the rates of prevalence were much higher as compared with the finding of the present study, and other research showed relative lower findings, even though the number of patients included in the respective studies differed: Nigeria (36.6%, 128/350) [28], Northwest Ethiopia (16.2%, 43/265) [29], South Ethiopia (36.5%, 150/411) [30], United States (10.3%, 1,551/15,126) [31], and Ethiopia (31.0%, 2,504/8,079) [32]. The above differences in anemia prevalence might be due variations in nutritional status of patients, their family histories, diseases caused by a genetic disorder, the presence of current co-infections caused by either parasites or other diseases that can contribute to the occurrence of anemia.…”
Section: Discussioncontrasting
confidence: 73%
“…This was comparable to 33.7% among same group of women from Jos, 44.6% from another study from Owerri, both in Nigeria, and 34.5% using Hb<10 g/dl cut-off from South Africa study. [30][31][32] The finding was however much lower than 62.6% prevalence found from Port Harcourt, 75.5% from Orlu, and 88.5% prevalence in Uyo, all from Nigeria, as well as 64.5% from South Africa, and 83.0% from Tanzania. [33][34][35][36] The high prevalence of anaemia in HIV positive pregnant women in this study could not be unconnected with multifactorial causes earlier mentioned: Direct retroviral infection of bone marrow stroma, and haematopoietic stem cells, changes in the regulation/suppression of erythropoiesis from cytokine production, and decrease in erythropoietin concentration, and indirectly from increase in apoptosis of the marrow cells in response to chronic opportunistic infections with autoimmune destruction of cells.…”
Section: Discussionmentioning
confidence: 67%